BIOECOLOGICAL AND BIOMORPHOLOGICAL FEATURES OF CLEAVING BEDSTRAW (GALIUM APARINE L.) - M.B. Toshmukhamedova; D.M. Alikarieva (Bright Mind Publishing, 2025)
This study presents a comprehensive analysis of literature sources and original observations on the biological, ecological, and morphological characteristics of Galium aparine L. (cleaving bedstraw) in the conditions of the botanical garden of Tashkent. Morphological traits of the plant, its life cycle, growing conditions, methods of reproduction, as well as the composition of biologically active compounds and their pharmacological significance, are considered. The study demonstrates the high adaptability of the species to various soil and climatic conditions and its potential both as a medicinal plant and as a weed. The article includes a literature review, tables of morphological and bioecological characteristics, and a description of the research methodology.
Keywords: Galium aparine L., bioecology, morphology, reproduction, botanical garden, laboratory conditions, biologically active compounds